Movement Boundary Shape of Overburden Strata and Its Influencing Factors - Changchun He; Jialin Xu; Fei Wang; Feng Wang (Energies, 2018)
Strata movement boundary is not only a parameter for the prediction of overburden strata movement and deformation but also a key index of setting shafts, roadways and protective coal pillars. Based on physical and mechanical properties of rock mass, the overburden strata are divided into bedrock and unconsolidated stratum. By means of theoretical analysis, physical simulation and numerical simulation, this paper studies the movement boundary shapes of bedrock and unconsolidated stratum, builds fitting equations of movement boundary of the two, analyzes the influence of key strata (KS) on the shape of strata movement boundary, and determines the principle of setting protective coal pillars. The results show that the movement boundaries of bedrock and unconsolidated strata are located at the outside of coal mining boundary. They are concave-upward power function curves that cannot be merged into a smooth one due to their different mechanisms of movement and deformation. The movement boundary of bedrock can approximate a straight line when lithology of the overburden is relatively uniform with thin strata in different positions; the surface movement boundary extends when the overburden has thick and stiff KS that are common in deeply buried coal seam. Therefore, the width of protective coal pillar is small if the movement boundary is regarded as a straight line. According to the curve movement boundary, the protective coal pillar for the passenger roadway of Panel 31010 of Pingdingshan No.1 mine is at least 99.4 m in width, larger than the designed one, which is the actual reason for its deformation and breakage.